ANALISIS SEKTOR-SEKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI KABUPATEN ACEH TAMIANG - Zikriatul Ulya; Zulfa Eliza; Achara Willyanda (Jurnal Samudra Ekonomika, 2022)
This study aims to determine the effect of the agricultural sector, the trade sector and the manufacturing sector on the economic growth of Aceh Tamiang Regency. to determine the effect of the agricultural sector, the trade sector and the manufacturing industry sector partially and simultaneously on the economic growth of Aceh Tamiang Regency. This study uses time series data with a time series from 2011-2021. This study uses a quantitative approach. This research model uses multiple linear regression method using SPSS 2.0 application. The results of the study with a significance level of 5% showed that the variables of the agricultural sector, the trade sector and the manufacturing sector had a positive and significant effect on the variable of economic growth in Aceh Tamiang Regency. Keywords: Agriculture Sector, Trade Sector, Manufacturing Sector, Economic Growth